Identification of human neutralization-inducing regions of the human immunodeficiency virus type 1 envelope glycoproteins. - Broliden, P A (1992)
Four major neutralizing regions of the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein were identified and characterized with a panel of 80 HIV-1 antibody-positive human sera. Levels of neutralizing antibodies against the HIV-1 strains IIIB, SF2, and RF were compared with reactivity in ELISAs against peptides that correspond to certain regions of the HIV-1 envelope. A correlation between high neutralizing activity and strong seroreactivity against specific peptides suggested that the corresponding regions might be involved in neutralization. This was further substantiated by using peptides to inhibit neutralization by a panel of 10 HIV-1 antibody-positive sera. The positions of three neutralizing sites, defined earlier mostly by antisera from animals, were confirmed in the present study. Human sera thus recognize the strain-specific third variable region of gp120 (amino acids 304-318), the C-terminal end of gp120 (amino acids 489-508), and the conserved region in the intracellular part of gp41 (amino acids 732-746). It is likely that these different regions mediate help rather than self-sufficient neutralization. Furthermore, a human neutralizing region was detected in a conserved part of gp41 (amino acids 647-671). Accordingly, neutralizing antibodies directed to this region were found to be cross-reactive between HIV-1 strains. Peptides corresponding to these four regions were able to inhibit neutralization mediated by serum from HIV-1 antibody-positive individuals. These results indicate that this conserved B-cell epitope of the HIV-1 envelope elicits a virus-neutralizing antibody response during natural infection in humans and may therefore be considered for inclusion in a vaccine against HIV-1.